2014
DOI: 10.1177/0333102414523843
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmoplegic migraine: From questions to answers

Abstract: OM is the same disease in adulthood and childhood, even if in adults the MR imaging findings are negative. In the authors' opinion, OM should be classified as migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 43 publications
0
25
0
2
Order By: Relevance
“…Postulated mechanisms include edema of the internal carotid artery within the cavernous sinus, edema of distal basilar artery, and ischemia or compression of the third nerve [63] or of recurrent demyelinating cranial neuropathy.…”
Section: Sodium Channelmentioning
confidence: 99%
“…Postulated mechanisms include edema of the internal carotid artery within the cavernous sinus, edema of distal basilar artery, and ischemia or compression of the third nerve [63] or of recurrent demyelinating cranial neuropathy.…”
Section: Sodium Channelmentioning
confidence: 99%
“…Most reported cases fully resolve in days to months, although there are case reports of longer lasting symptoms following multiple attacks. 36 OM creates much conflict in the literature. A recent review 37 found that in up to one-third of cases the associated head pain was not migrainous in quality and neither were there associated migrainous symptoms, such as nausea or vomiting.…”
Section: Ophthalmoplegic Migrainementioning
confidence: 99%
“…The childhood variant, however, may be a cranial neuropathy. Ambrosetta and colleagues 36 hypothesized that these attacks in adults and children are the same disorder. They believed OM is migrainous and caused by ischemic reversible breakdown of the bloodÀnerve barrier due to vasospasm during the attack.…”
Section: Ophthalmoplegic Migrainementioning
confidence: 99%
“…Chronic tension headache and Migraine are the most common causes of headache noted in population-based survey on the prevalence of headache in the state of Karnataka [2]. Besides these common causes there are other causes for headache like trauma, infection, tumor, vascular, alcohol or drug abuse or may be related to ophthalmoplegic migraine [3].…”
Section: Introductionmentioning
confidence: 99%